2010
DOI: 10.5539/jas.v2n1p48
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Drying Temperature on the Hygroscopicity of Rubberwood (Hevea Brasiliensis)

Abstract: The influence of drying temperature on the hysteresis effect of rubberwood is determined in this study. Results showed reductions in sorption capacity of rubberwood dried at high temperatures as compared to the control conventional temperature dried material at respective corresponding set conditions. The reduction of the hygroscopicity of rubberwood is a combined effect of both physical, morphological structure and chemical composition as affected by the drying temperature. This improvement is found to be pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…than of other wetland Poaceae, such as Glyceria maxima and Phalaris arundinacea (Schoelynck et al, 2010). Heat treatments cause physical, chemical and morphological modifications in wood tissue leading to changes in stability, diffusibility (Hillis, 1984) and sorption capacity (Sik et al, 2010). Furthermore, increased deacetylation (Tjeerdsma and Militz, 2005) and phenol content (Ayadi et al, 2003) have been observed following heat-treatments.…”
Section: Discussionmentioning
confidence: 97%
“…than of other wetland Poaceae, such as Glyceria maxima and Phalaris arundinacea (Schoelynck et al, 2010). Heat treatments cause physical, chemical and morphological modifications in wood tissue leading to changes in stability, diffusibility (Hillis, 1984) and sorption capacity (Sik et al, 2010). Furthermore, increased deacetylation (Tjeerdsma and Militz, 2005) and phenol content (Ayadi et al, 2003) have been observed following heat-treatments.…”
Section: Discussionmentioning
confidence: 97%
“…The increase in the peak heights of the heat treated wood samples compared to untreated wood samples as shown in Fig. 2 indicates an increase in crystallinity and this increase in crystallinity might be attributed to the loss of hemicelluloses and degradation/rearrangement of amorphous cellulose content [33,34].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…It has been hypothesized that noncrystalline cellulose forms hydrogen bonds with cellulose at the surface of crystalline region due to the repeated moisture changes (Toba et al 2013). Drying at high temperatures also results in the cellulose crystallization in the noncrystalline region (Rayirath et al 2008, Sik et al 2010. Drying does not alter cellulose crystallinity or cellulose crystalline structure, though it affects the size of microfibril bundles and thus the cellulose accessibility to water (Sik et al 2010).…”
Section: Crystallinitymentioning
confidence: 99%
“…Drying at high temperatures also results in the cellulose crystallization in the noncrystalline region (Rayirath et al 2008, Sik et al 2010. Drying does not alter cellulose crystallinity or cellulose crystalline structure, though it affects the size of microfibril bundles and thus the cellulose accessibility to water (Sik et al 2010). Random (cold) crystallization in the quasi-crystalline region of wood cellulose may also increase the crystallinity of wood.…”
Section: Crystallinitymentioning
confidence: 99%